Seeing the Media Education from the Lens of Critical Discourse Analysis - Saragi, Veronica; Septiani, Annisa; Jumiati, Jumiati (Universitas Lancang Kuning, 2020)
This paper is about critical discourse analysis (CDA) in media education. Students have used mass media to help them to learn. With the wide reaching access of the world wide web, they can receive all sorts of information from it. Although mass media can help the students to learn, mass media also has an adverse effect. For that, the students must know how to critically mass media such as the theory of critical media literacy and the practice of being critical towards information.